(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is written in order to study the features of the interrogation of minors, namely the definition of specific specialists who must be present during the interrogation. The norms of the current criminal procedure legislation and the work of domestic scientists who considered the outlined issue are analyzed. The article highlights the author’s vision of specifying some norms of procedural legislation. Ways of improving the legislation regulating the participation of a specialist during the interrogation of minors are proposed. Based on the analysis, it is determined that in most cases it is advisable to involve a psychologist during the interrogation of a minor. A psychologist is a specialist who understands the psycho-emotional processes of children. The teacher, unlike the psychologist, should teach children, give them knowledge. During interrogation, the psychologist helps the investigator formulate questions that should be asked to the minor. Such a specialist can help create a trusting environment during interrogation and prevent pressure on the child or intimidation. The current Criminal Procedure Code of Ukraine does not contain a specific definition of which specialist should be chosen to conduct investigative actions with the participation of a minor. The legislator left this choice to the investigator. The investigator determines who to invite - a psychologist or teacher. That is why sometimes the presence of a teacher who does not understand child psychology becomes a simple formality. The lack of the necessary specialist negatively affects the results of the interrogation. According to the author, special attention should be paid to the choice of a psychodog if the child is a victim in a criminal case. Incorrectly asked questions or conducted investigative actions can harm the child, force him to mentally return to the crime. Such testimony and evidence may be false or have no evidentiary value to the case. Also, incorrect actions on the part of the investigator can harm the psychological state of the child. It should be noted that in order to establish the necessary psychological contact, to ensure a benevolent atmosphere when interrogating persons who committed a socially dangerous act before they reach the age of criminal responsibility, as well as those who have reason to consider mentally retarded, it is more expedient to involve a psychologist rather than a teacher.